Editorial - Pacheco Romero, José (2015)
The diploid fungus, polymorph, Candida albicans is one the most important pathogenic fungi of man. It can grow, proliferate and coexist as above or diner within the host for long. Alterations in host environment can do so virulent. There is a conversation immunological cross between C. albicans and man's innate immune system that may be affected by stressors such as limited nutrition, pH, temperature, between others, causing response mechanisms and evasion mushroom (1). That is, the lifestyle of C. albicans depends its ability to be modified genetically and epigenetically of quickly in response to specific signals from the environment (2). This ability to turn their cell forms contributes its ability to infect different host niches and strictly regulate sexual mating program (3). Therefore it can cause nuisance acute skin infections and mucous membranes, and severe invasive infections, many diseases associated with decreased immunity. In search for alternatives to drugs and antifungals its side effects, Article Thymus essential oil L vulgaris (thyme), its combination with EDTA against Candida albicans and formulation of a cream, determines the activity thyme oil and its combination with EDTA on Candida albicans and a cream formulated with oil supplemented with natural terpene derivatives. Oil EDTA alone and essential in the cream - formulated in the cream - inhibited the growth of Candida albicans, no signs of toxicity skin in rabbits.